Comparison of passive flow control methods for a cavity in transonic flow - Saddington, Alistair J.; Thangamani, Varun; Knowles, Kevin (AIAA, 2016)
Acomparative study of different passive control techniques was conducted on a cavity with a length of 320mmwith length-to-depth and length-to-width ratios of five and two, respectively. The tests were conducted at a freestream Mach number of 0.71. Both leading-edge and trailing-edge modifications were included in the studies. Results from surface pressure measurements showed that leading-edge control techniques were more effective at suppressing cavity tone amplitudes than trailing-edge modifications.Asquare-tooth spoiler showed the greatest reduction in tonal amplitude (8.8 dB); however, a sawtooth spoiler showed the greatest reduction in overall sound pressure level (8.13 dB). Velocity measurements inside the cavity were made using particle image velocimetry for the clean cavity and the cavity with sawtooth spoilers. The results showed a reduction in momentum exchange between the freestream flow and the cavity when spoilers were used. This is proposed to be the main reason for the reduced tonal amplitudes.
Keywords: Trailing Edges; Passive Control; Overall Sound Pressure Level; Freestream Mach Number; Particle Image Velocimetry; Transonic Flow; Boundary Layer Thickness; Transonic Wind Tunnel; Adverse Pressure Gradient; Static Pressure